Marital trajectories and women's wellbeing in Senegal - Sylvie Lambert; Dominique Van de Walle; Paola Villar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Divorce and widowhood followed by remarriage are common for women in Africa. A key question is how such discontinuous marital trajectories affect women's wellbeing. Women's marital trajectories in Senegal are described and correlated with measures of voice, resource constraints, and wellbeing as measured by consumption. Considerable selection into divorce and widowhood as well as subsequent remarriage is documented. Poorer women are more vulnerable to both dissolution and remarriage, and hence bear more of the costs while being nevertheless afforded a safety net in the form of a male protector. Marital breakdowns and their aftermaths are far from neutral in terms of women's wellbeing.
Keywords: J12; I31; J16; 330; divorce; Senegal; welfare; widowhood; women